2012
DOI: 10.1016/j.canlet.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi sarcoma-associated herpesvirus (KSHV) induces a functional tumor-associated phenotype for oral fibroblasts

Abstract: The Kaposi sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi sarcoma (KS), the most common HIV/AIDS-associated tumor worldwide. Involvement of the oral cavity portends a poor prognosis for patients with KS, but mechanisms for KSHV regulation of the oral tumor microenvironment are largely unknown. Infiltrating fibroblasts are found with KS lesions, and KSHV establishes latent infection within human primary fibroblasts in vitro, but contributions for KSHV-infected fibroblasts to the KS micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 28 publications
3
29
1
3
Order By: Relevance
“…Microarray analyses have revealed upregulation of Egr2 in metastatic squamous cell carcinomas (Kim et al, 2006;Liu et al, 2008). Furthermore, in fibroblasts infected with Kaposi sarcoma-associated herpesvirus, Egr2 induces MMPs and extracellular matrix metalloproteinase inducer (Emmprin) (Dai et al, 2012). These observations strongly support the proposal that Egr2 is a key regulator of glioma invasion.…”
Section: Fret-based Cell Sortingsupporting
confidence: 59%
“…Microarray analyses have revealed upregulation of Egr2 in metastatic squamous cell carcinomas (Kim et al, 2006;Liu et al, 2008). Furthermore, in fibroblasts infected with Kaposi sarcoma-associated herpesvirus, Egr2 induces MMPs and extracellular matrix metalloproteinase inducer (Emmprin) (Dai et al, 2012). These observations strongly support the proposal that Egr2 is a key regulator of glioma invasion.…”
Section: Fret-based Cell Sortingsupporting
confidence: 59%
“…Recent studies demonstrated compelling evidence that de novo KSHV infection of human endothelial cells as well as oral and fore-skin-derived fibroblasts results in upregulated expression of CD147 and that this effect is directly associated with various virological outcomes consistent with a pro-invasive, migratory, and pro-angiogenic phenotypes (Qin et al, 2010; Dai et al, 2012a,b). We have also found that KSHV upregulates CD147 not only in melanoma-derived cells but also in chronically infected lymphatic, microvascular, and brain endothelial cells (e.g., see Figure 4 ).…”
Section: Cd147 and Kshv Pathogenesismentioning
confidence: 99%
“…In cell culture, KSHV is able to infect various types of human cells, such as B cells, endothelial cells, epithelial cells, and fibroblasts (Dai et al, 2012; Fontana et al, 2014; Kang and Myoung, 2017). Several membrane proteins including heparin sulfate proteoglycan (HSPG), DC-SIGN, integrin α3β1/αvβ3, EphA2 and xCT can act as cellular receptors for KSHV infection in a cell type-dependent manner (Birkmann et al, 2001; Akula et al, 2002; Kaleeba and Berger, 2006; Rappocciolo et al, 2006; Garrigues et al, 2008; Hahn et al, 2012).…”
Section: Role Of Lipids In the Primary And Latent Kshv Infectionmentioning
confidence: 99%